How inclusive were strategies to prevent the spread of COVID-19 for people with disabilities? Evidence from qualitative research in eight low- and middle-income countries - Xanthe Hunt; Sarah Marks; Shaffa Hameed; Donruedee Srisuppaphon; Francisco Diez-Canseco; Wachara Riewpaiboon; Shaheda Viriyathorn; Viroj Tangcharoensathien; Divya Goyal; Tracey Smythe; Rifat Shahpar Khan; Luong Anh Ngoc; et al. (International Journal for Equity in Health)
Abstract Background From the outset of the pandemic there were calls to ensure people with disabilities were included in prevention and response measures, given their increased risk of health consequences from COVID-19 infection. This study sought to explore people with disabilities’ experiences of inclusion in the response to the COVID-19 pandemic, to understand how such responses can be more inclusive in the future. Methods Qualitative interviews were conducted with 372 people with disabilities and their caregivers in Bangladesh, Ghana, India, Peru, Thailand, Türkiye (with Syrian refugees), Viet Nam, and Zimbabwe between 1 December 2020 and 28 February 2023, and analysed using thematic analysis. Results The study found that people with disabilities demonstrated high levels of knowledge about COVID-19 and were willing to adhere to prevention measures. However, participants noted that countries’ COVID-19 responses were largely not inclusive of people with disabilities; that pandemic information was seldom available in accessible formats; and that adhering to social distancing and other mandates was challenging and incurred personal and economic costs. Conclusions Consequently, the pandemic compounded existing barriers and inaccessibility experienced by people with disabilities and contributed to inequality.